THE RELATIONSHIP BETWEEN PARENTAL ATTACHMENT AND INDEPENDENCE IN MIGRANT ADOLESCENTS: A STUDY OF PSYCHOLOGY STUDENTS AT UNIVERSITAS PRIMA INDONESIA - Katherine; Nabila Nur Irslan; Audrey Griselda; Angel; Achmad Irvan Dwi Putra; Winida Marpaung (RADJA PUBLIKA, 2026)
Parental attachment is one of the key factors influencing the development of adolescent independence, particularly among adolescents who live away from their families. This study aims to examine the relationship between parental attachment and independence among adolescents living away from home in the Faculty of Psychology. The respondents in this study were adolescents aged 17–21 years who lived apart from their parents. The research sample consisted of 233 respondents selected using a purposive sampling technique. The data were analyzed using the Pearson Product Moment correlation test, which yielded a correlation coefficient of r = 0.266 with p = 0.000 (p < 0.05). The results indicate a positive and significant relationship between parental attachment and independence among adolescents living away from home. This means that the higher the level of parental attachment perceived by adolescents, the higher their level of independence, and vice versa. These findings can serve as a basis for designing emotional support programs for adolescents living away from home to enhance independence through strengthening parent–child relationships.